Advanced oxidation using modified enteromorpha algae-derived biochar for marine sediment dehydration - Lun Tan; Jian Zhang; Jiaoyang Du; Lianjie Guo; Hong Deng; Ying-Ying Gu (Frontiers in Chemistry)
IntroductionThis study aims to enhance the dewatering performance of marine sediment using modified Enteromorpha algae-derived biochar to activate persulfate through an advanced oxidation process. Dehydration of marine dredged sediment is a challenging issue in the field of environmental remediation. Traditional dewatering methods are often inefficient due to the high water content, high Cl⁻ levels, and large volume of marine sediment.MethodsTo address this, we developed an effective and environmentally friendly dewatering approach using biochar as a conditioning agent in combination with the strong oxidizing properties of persulfate. The biochar was prepared by pyrolyzing Enteromorpha algae at high temperatures and modified with FeSO4 solution to enhance its dewatering performance.ResultsThe results showed that under the optimal conditions of adding 4% of modified biochar and 1% of persulfate, the specific resistance to filtration (SRF) of sediment decreased by 73.4%, the yield of net solid (YN) increased by 105%, and the dehydration amount increased by 118%.DiscussionThe mechanism underlying the improved dehydration performance of marine sediment was revealed through the analysis of extracellular polymeric substances (EPS), zeta potential, compression coefficient changes, and microstructure analysis. It was found that Fe2+ compressed the double electric layer of sediment, while the activation of persulfate generated ·OH and SO4−· that effectively degraded EPS, thereby enhancing the dewatering performance. This research not only provides a new strategy for the sustainable treatment of marine sediment but also offers a theoretical basis for the resourceful utilization of algal biomass.